Gluteal Compartment Syndrome Secondary to Pelvic Trauma - Fernando Diaz Dilernia; Ezequiel E. Zaidenberg; Sebastian Gamsie; Danilo E. R. Taype Zamboni; Guido S. Carabelli; Jorge D. Barla; Carlos F. Sancineto (Case Reports in Orthopedics, 2016)
Gluteal compartment syndrome (GCS) is extremely rare when compared to compartment syndrome in other anatomical regions, such as the forearm or the lower leg. It usually occurs in drug users following prolonged immobilization due to loss of consciousness. Another possible cause is trauma, which is rare and has only few reports in the literature. Physical examination may show tense and swollen buttocks and severe pain caused by passive range of motion. We present the case of a 70-year-old man who developed GCS after prolonged anterior-posterior pelvis compression. The physical examination revealed swelling, scrotal hematoma, and left ankle extension weakness. An unstable pelvic ring injury was diagnosed and the patient was taken to surgery. Measurement of the intracompartmental pressure was measured in the operating room, thereby confirming the diagnosis. Emergent fasciotomy was performed to decompress the three affected compartments. Trauma surgeons must be aware of the possibility of gluteal compartment syndrome in patients who have an acute pelvic trauma with buttock swelling and excessive pain of the gluteal region. Any delay in diagnosis or treatment can be devastating, causing permanent disability, irreversible loss of gluteal muscles, sciatic nerve palsy, kidney failure, or even death.